(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Abstract: Medicinal plants have been used for centuries to treat various ailments and promote well-being. This article covers the process of extracting medicinal plants, a systematic approach that maximizes their therapeutic benefits.